2022
DOI: 10.7759/cureus.32467
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Philadelphia Positive Acute Lymphoblastic Leukemia in Adolescent and Young Adults

Abstract: BackgroundPhiladelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) accounts for 25% of acute lymphoblastic leukemia cases in the adolescent and young adult (AYA) age subgroup. It is associated with poor outcomes and is considered a standard indication for allogeneic stem cell transplant (Allo-SCT). Improved outcomes have been reported with addition of tyrosine kinase inhibitors (TKIs) to chemotherapy in children and the role of Allo-SCT is now being debated in the first remission. Complete respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A study by Ravandi et al reported that 31 out of 72 patients considered eligible for the Hyper-CVAD plus dasatinib trial received fewer than the intended 8 cycles due to poor tolerance [59]. Some publications have also noted excessive toxicity during consolidation, which appears to be associated with the choice of chemotherapy prescribed in these block [12,59,60]. High doses of methotrexate (MTX) and cytarabine (HD-AraC) are typically administered, along with anthracyclines, cyclophosphamide, and clofarabine in some protocols.…”
Section: Consolidation and Maintenance Therapymentioning
confidence: 99%
“…A study by Ravandi et al reported that 31 out of 72 patients considered eligible for the Hyper-CVAD plus dasatinib trial received fewer than the intended 8 cycles due to poor tolerance [59]. Some publications have also noted excessive toxicity during consolidation, which appears to be associated with the choice of chemotherapy prescribed in these block [12,59,60]. High doses of methotrexate (MTX) and cytarabine (HD-AraC) are typically administered, along with anthracyclines, cyclophosphamide, and clofarabine in some protocols.…”
Section: Consolidation and Maintenance Therapymentioning
confidence: 99%